2016
DOI: 10.1186/s12970-016-0150-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of six days of dietary nitrate supplementation on performance in trained CrossFit athletes

Abstract: BackgroundWhile it is well established that dietary nitrate reduces the metabolic cost of exercise, recent evidence suggests this effect is maintained 24 h following the final nitrate dose when plasma nitrite levels have returned to baseline. In addition, acute dietary nitrate was recently reported to enhance peak power production. Our purpose was to examine whether chronic dietary nitrate supplementation enhanced peak power 24 h following the final dose and if this impacted performance in a heavily power-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(119 citation statements)
references
References 28 publications
4
109
4
2
Order By: Relevance
“…To compare the performance changes between the 30-s and 60-s tests, the percent change (∆) between the experimental and placebo supplements was calculated for the 30- In contrast to the findings of this study, Kramer et al, (2016) found an increase in peak power during a 30-s Wingate from pre-to post-supplementation with 8 mmol•day -1 potassium NO3-. Some key differences should be noted when comparing the present study to Kramer et al's (2016) work.…”
Section: Comparison Of 30-s Vs 60-s Testscontrasting
confidence: 49%
See 4 more Smart Citations
“…To compare the performance changes between the 30-s and 60-s tests, the percent change (∆) between the experimental and placebo supplements was calculated for the 30- In contrast to the findings of this study, Kramer et al, (2016) found an increase in peak power during a 30-s Wingate from pre-to post-supplementation with 8 mmol•day -1 potassium NO3-. Some key differences should be noted when comparing the present study to Kramer et al's (2016) work.…”
Section: Comparison Of 30-s Vs 60-s Testscontrasting
confidence: 49%
“…Peak power during a Wingate cycling test improved with 8 mmol KNO3 supplementation versus a control (948.08 ± 186.80 W vs. 889.17 ±179.69 W), with no differences in mean power (Kramer et al, 2016). These results suggest that not only can dietary NO3-possible enhance peak power, but it can be effective if taken 24 hours or more prior to an event.…”
Section: Anaerobic Exercisementioning
confidence: 52%
See 3 more Smart Citations